Innovation choices in modern times: the interplay of technology and non-technology approaches with a spotlight on the moderation effect of research systems - Anderson, Henry Junior; Odei, Samuel Amponsah; Frimpong, Bright; Stejskal, Jan; Febiri, Frank (Inderscience Enterprises Ltd, 2024)
Recently, businesses have increasingly adopted open innovation, yet many still opt for internal innovation due to trust, security, and cost concerns. Notwithstanding, there has been little research into these strategic choices' immediate and long-term effects. This study addresses this gap by analysing data from the European Innovation Scoreboard between 2011 and 2019. We investigate whether a firm's decision to pursue internal or open innovation significantly impacts its technological and non-technological innovation outcomes over varying timeframes. Additionally, we examine the contingent influence of a research system on firms' decisions regarding innovation collaboration. Our findings reveal that internal and open innovation strategies have distinct effects on small and medium-sized enterprises (SMEs) across different periods, particularly with a two-year time lag. Further, a robust research system can impede cooperative efforts to achieve technological and non-technological innovation objectives. The study concludes with practical policy recommendations, empowering businesses with clear guidance for navigating innovation strategies in current business environments.
Inovační volby v moderní době: souhra technologických a netechnologických přístupů se zaměřením na efekt výzkumných systémů
Keywords: technological innovation; non-technological innovation; human capital; open innovation; in-house innovation; technologická inovace; netechnologická inovace; lidský kapitál; otevřená inovace; interní inovace